Pengembangan Bahan Ajar Jaringan Komputer berbasis Somatis, Auditori, Visual dan Intelektual (SAVI) - Yadi Yadi; Siti Aminah (Universitas Hamzanwadi, 2023)
The government has made improvements to the learning system through changes to the curriculum to produce a generation that is ready to compete in an era of progress and the future. The focus is not only on increasing knowledge, innovation in teaching materials must continue to be carried out by teachers to create an active, interactive, and fun learning environment as well as provide space for students to develop their potential. The research aims to develop innovative SAVI (Somatic, Auditory, Visual, and Intellectual) based Computer Network teaching materials. This research method uses a research and development approach by following the ADDIE development used consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques include interviews, documentation, observation, and literature study and instruments whose results are analyzed using descriptive statistics. The results of developing computer network teaching materials using the SAVI approach in the learning process show a validity result of 0.87 and a practicality test of 4.52 so that the teaching materials developed can be applied to computer network learning. Therefore, the development of SAVI-based teaching materials contributes to the development of innovative teaching materials in education.